Effects of mediators for ligninolytic enzyme production and kinetic studies on degradation of pentachlorobenzene by trametes versicolor U80 - Sari, A. A. (Springer International Publishing, 2016)
Pentachlorobenzene is one new persistent organic pollutants (POPs) that has been recently added to the Stockholm Convention on Persistent Organic Pollutants. Based on this reason, one treatment having ability to degrade this compound is needed. The microbiological process by using white-rot fungus was used in this experiment. Free cell of Trametes versicolor U80 degraded pentachlorobenzene 43 % in liquid medium at 40 days incubation. The rapid initial uptake of pentachlorobenzene was obtained in the first 20 days. The results based on ionization potential and the partial least square function indicated that both enzymatic systems of lignin peroxidase and P-450 monooxygenase involved in the degradation of pentachlorobenzene. By using addition of Tween 80, MnSO4, and veratryl alcohol, degradation of pentachlorobenzene could be improved. Based on kinetic study, the use of 1 % of Tween 80 showed the highest degradation rate (2.0619/day) and the degradation of pentachlorobenzene by 50 % can be shortened up to 24 days. Application of T. versicolor U80 in soil and bioreactor degraded pentachlorobenzene 43 and 50 % at 40 days, respectively. T. versicolor U80 shows good capability degrading pentachlorobenzene in soil and bioreactor although it is lower than in liquid due to the difference of pollutant accessibility and transfer oxygen. Finally, strain T. versicolor U80 can be proposed as an excellent candidate for remediation application in pentachlorobenzene pollution.